Electronic Voting System: Preliminary Study - Ibrahim, Subariah; Salleh, Mazleena; Kamat, Maznah (Penerbit UTM Press, 2000)
Election is a democratic process that allows a citizen to vote for a ruling government. This paper first reviews the evolution of a voting system and how an election process is carried out. It then focuses on the discussion of the security requirements for a reliable electronic voting system and how these requirements are implemented in several electronic voting system. This paper also compares the implementation of electronic voting system with a traditional voting system